Polarisasi “Liyan” dalam Meme Please Help Me: Contraceptive Pills - Dwi Oktalina Lestari (Calathu: Jurnal Ilmu Komunikasi, 2021)
Contraceptives are considered to be the key to solving poverty problems by controlling women's reproductive systems. In campaigning for poverty solutions, women's bodies are presented in the Please Help Me: Contraceptive Pills meme through a representation system. Representation is closely related to the use of stereotypes which are subjective and prejudiced labeling. The first discussion is about how women's cultural identity is represented in the sign relation of a Please Help Me: Contraceptive Pills meme and what ideological practices that works behind the meme. This paper aims to analyze the representation system of women's cultural identity in a meme, Please Help Me: Contraceptive Pills. In addition, this paper seeks to show the pervasive discrimination through sign relations. This qualitative research uses the semiotic method in interpreting signs in memes. The results of this analysis state that the practice of the representation system has limited the flow of meaning so that in this meme there is an imbalanced represention of women's cultural identity and that the responsibility for procreation is only a woman's concerns. Keywords: discrimination, identity, meme, representation, the Other